Use of Stroop Test for Sports Psychology Study: Cross-Over Design Research - Takahashi, Shinji; Grove, Philip M. (Frontiers in Psychology, 2020)
Background: In sports psychology research, the Stroop test and its derivations are commonly used to investigate the benefits of exercise on cognitive function. The measures of the Stroop test and the computed interference often have different interclass correlation coefficients (ICC). However, the ICC is never reported in cross-over designs involving multiple variances associated with individual differences. Objective: We investigated the ICC of the Stroop neutral and incongruent tests and interference (neutral test - incongruent test), and reverse Stroop task using the linear mixed model. Methods: Forty-eight young adults participated in a cross-over design experiment composed of 2 factors: exercise mode (walking, resistance exercise, badminton, and seated rest as control) and time (pre- and post-tests). Before and after each intervention, participants completed the Stroop neutral and incongruent, and the reverse-Stroop neutral and incongruent tests. We analyzed for each test performance and interference and calculated ICC using the linear mixed model, Results: The linear mixed model found a significant interaction of exercise mode and time for both the Stroop and reverse-Stroop tasks, suggesting that exercise mode influences the effect of acute exercise on inhibitory function. On the other hand, there was no significant effect of exercise mode for both the Stroop and reverse-Stroop interference. The results also revealed that calculating both the Stroop and reverse-Stroop interference resulted in smaller ICCs than the ICCs of the neutral and incongruent tests for both the Stroop and reverse-Stroop tasks. Conclusions: The Stroop and reverse-Stroop interferences are known as valid measures of the inhibitory function for cross-sectional research design. However, to understand the benefits of acute exercise on inhibitory function comprehensively by cross-over design, comparing the incongruent test with the neutral test also seems superior because these tests have high reliability and statistical power.